Analisis Komparatif Model Altman Z-Score, Springate, Zmijewski Sebagai Alat Ukur Potensi Kebangkrutan - Joni Hendra; Tatik Amani (STIE Mandala Jember, 2020)
The study was conducted with the aim to determine the effective measurement of bankruptcy by comparing the Altman (Z-Score), Springate, and Zmijewski methods in the Consumer Goods Industry listed on the Indonesia Stock Exchange (IDX) in 2016 -2018. This type of research is quantitative, with the variable bankruptcy, Altman (Z-Score), Springate, and Zmijewski. This type of research is quantitative, with the variable bankruptcy, Altman (Z-Score), Springate, and Zmijewski. The population of this study is the Consumer Goods Industry sub-sector food and beverages with sample selection using purposive sampling so that eleven companies are obtained that meet the sample criteria.The results showed that the calculation results from the Altman Z-Score method were supported by the Springate method because most of them showed relatively similar results. As for the Zmijewski method, the calculation results tend to be different from the other two methods. This can be seen from all companies that are in a safe condition, while the Altman and Springate methods, there is one company that has been declared bankrupt for three periods, namely PT Tri Banyan Tirta Tbk. Keywords:Altman, Springate, Zmijewski, Bankruptcy